'Can you see me? All of me?' Performing the child soldier in Congo My Body. (1st April 2017) - Messay, Marda
This article examines Congo My Body, an autobiographical performance performed in 2011 at the festival Hautes Tensions de La Villette in Paris, France, by former Congolese child soldiers Serge Amisi and Jean René Yaoundé Mulamba, and choreographer Djodjo Kazadi. In this work, the three performers recreate Amisi and Mulamba's experiences as child soldiers in Joseph Kabila's army from 1997 to 2001. After establishing the stereotypical and oftentimes narrow western representations of child soldiers as a starting point, this article identifies how the performers use the performance space to bridge the perceived otherness of the child soldier and position the audience as witnesses. Through the use of their own bodies and puppets, the performers not only recreate the child soldiers' indoctrination into violence and its traumatic and devastating effects but also blur the line between victim and aggressor. This article argues that with Congo my Body, the performers attempt to make the spectators aware of their own perception of child soldiers and encourage the audience to reflect on the child soldiers' fate beyond the performance.